Strategies of Translating Phraseological Units (on the Interview of Vladimir Putin to Tucker Carlson) - Yulia Y. Klykova; Irina Y. Shachkova (Этническая культура, 2024)
The article is devoted to the analysis of the functioning of linguistic units in socio-political texts. The authors of the article are interested in studying phraseological units in political discourse. Phraseologisms as a means of expressing expressiveness and implementing the pragmatic function of language are used by politicians to influence public and personal consciousness and, in some cases, to agitate for action. The aim of the research is to determine the strategies of translating phraseological units used by the Russian President Vladimir Putin in his interview with American journalist Tucker Carlson. In order to achieve this aim we conducted a comparative analysis of the most frequent ways of translating fixed phrases from Russian into English, and we also analysed the problems faced by simultaneous interpreters while translating them. The research was performed by the random sampling technique along with descriptive analysis and contextual interpretation methods. As a result of the analysis, we can make a conclusion that Vladimir Putin’s speech is characterized by national cultural features, abundant use of metaphors, phraseological units and occasional phraseologisms. At the same time, we have identified the most common strategy of translating phraseological units – the phraseological analogy, which makes it possible to identify translation equivalents that are different in form and image, but similar in content and meaning for the recipient culture.